Some wear leather, some wear lace : the worldwide compendium of postpunk and goth in the 1980s - Harriman, Andi; Bontje, Marloes (Intellect Books, 2014)
It was a scene that had many names: some original members referred to themselves as punks, others new romantics, new wavers, the bats, or the morbids. 'Goth' did not gain lexical currency until the late 1980s.